2004
DOI: 10.1017/s0012162204001434
|View full text |Cite
|
Sign up to set email alerts
|

Altered pathways for auditory discrimination and recognition memory in preterm infants

Abstract: Preterm infants are at increased risk for cognitive disorders, including impairments in recognition memory. This study evaluated the effects of extreme prematurity on the neural pathway for auditory recognition memory using event-related potentials (ERPs), a neurophysiological technique widely used in cognitive neuroscience. ERPs were recorded at term postmenstrual age in 35 preterm infants born at less than 32 weeks' gestation (22 males, 13 females; mean birthweight ([BW] 1154g, SD 374g) with normal brain ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 47 publications
(35 reference statements)
0
43
0
1
Order By: Relevance
“…Studies on communicative -linguistic development found that preterm children have problems in auditory discrimination in the first days of life, and at 4 and 5 years old (53,55,62), problems in grammar skills at 2, 3, 5 and 6 years old (47,50,55,57,59,61,64), problems in naming objects and words at 4 and 5 years old (55,62,63,64) and pre-reading skills at 6 years (64). Other studies found that these children have no problems in lexical production at 4 years old (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on communicative -linguistic development found that preterm children have problems in auditory discrimination in the first days of life, and at 4 and 5 years old (53,55,62), problems in grammar skills at 2, 3, 5 and 6 years old (47,50,55,57,59,61,64), problems in naming objects and words at 4 and 5 years old (55,62,63,64) and pre-reading skills at 6 years (64). Other studies found that these children have no problems in lexical production at 4 years old (62).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to full-term children, it has been found that in the first few days from birth, preterm children show atypical neural activity patterns during auditory discrimination activities and recognition of sounds, and also do not recognize their mother's voice (53).…”
Section: Communicative-linguistic Development Studiesmentioning
confidence: 99%
“…Significant delays have been found in auditory brainstem responses of preterm infants at a term-equivalent age, reflecting atypical brainstem maturation [4]. This is apparent even in preterm infants with normal brain ultrasound scans [5], which is believed to be attributable to exposure to the extrauterine environment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate differences in cortical potentials between term and preterm newborns (26,27) . Such fact was not observed in this study, since the maturation of the auditory pathway was similar in both groups, which can be justified due to the fact that the development depends on the stimulation received by the child, the environment in which he/she is inserted and possible complications along his/her development (12,13,14,15) .…”
Section: Discussionmentioning
confidence: 99%